Effect of Purple Corn Anthocyanin on Antioxidant Activity, Volatile Compound and Sensory Property in Milk During Storage and Light Prevention - Tian, Xing-Zhou; Wang, Xu; Ban, Chao; Luo, Qing-Yuan; Li, Jia-Xuan; Lu, Qi (Frontiers in Nutrition, 2022)
The aim of this study was to observe the effect of purple corn anthocyanin on the light-induced antioxidant activity, free radicals, volatile compounds, color parameters, and sensory properties of milk during storage. There were four groups: (1) negative control, no addition of anthocyanins + exposure to fluorescent light (NC); (2) positive control 1, no addition of anthocyanins + protected from fluorescent light (PC1); (3) positive control 2, the addition of 0.3% (w/v) anthocyanins + exposure to fluorescent light (PC2); and (4) the addition of 0.3% anthocyanins + protected from fluorescent light (AC). The results indicated that the AC group displayed a higher level of antioxidant activity in milk. The concentration of antioxidant activity parameters in the NC group decreased during the entire storage period, whereas antioxidant activity parameters were unchanged except for the glutathione peroxidase (GSH-Px) in the AC group. Moreover, the NC group showed lower levels of 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity and higher levels of superoxide anion and hydrogen peroxide than the other groups. The extent of malondialdehyde accumulation and lipid peroxidation in the control groups were greater than that of the AC group. Twenty-two volatile compounds were determined in milk, which consisted of eight alcohols, three ketones, five aldehydes, two esters, and four hydrocarbons by headspace gas chromatography mass spectrometer analysis. Specifically, individual aldehydes, esters and hydrocarbons in the AC group remained at relatively stable values during storage relative to the other three groups. Stronger positive correlations were noted between several antioxidant activities (superoxide dismutase, GSH-Px) and DPPH scavenging activity as well as total ketones in milk. Adding of anthocyanin did not impact on the color values of L*, a* and b* in light-protected milk during the entire storage period. Some sensory evaluation parameters (flat, garlic/onion/weedy, oxidized-light, oxidized-metal, rancid) in AC group were significantly higher than that of the control group at the end of the period. In conclusion, the current study revealed that the addition of purple corn anthocyanin pigment to light-protected milk had no negative effect on the sensory qualities, while it had the potential to prevent lipid oxidation, enhance antioxidant activity and maintain volatile compounds.